Interplay between barrier epithelial cells and dendritic cells in allergic sensitization through the lung and the skin. Issue 1 (July 2017) - Deckers, Julie; De Bosscher, Karolien; Lambrecht, Bart N; Hammad, Hamida
Summary: The prevalence of asthma is increasing over the years and it has become obvious that a thorough understanding of mechanisms leading to Th2 sensitization and to asthma is urgently needed to provide better ways to treat the disease. This articles reviews the different players involved in the initiation of allergic reactions in the lung and in the skin, and highlights the importance of a crosstalk between antigen‐presenting dendritic cells and structural cell‐derived signals in this process. Our increasing understanding of these mechanisms indicates that structural cells, such as airway epithelial cells and skin keratinocytes, need to be considered as more than a simple physical barrier since they are very upstream of the entire Th2 cascade and therefore might represent crucial targets for new therapies.